“Implementación de un sistema automatizado para el proceso de secado de cacao en el centro de acopio “Asoprocanam” del cantón La Maná.” - Gavilanez Ayala, Limber Paul (2021)
The purpose of this project was the implementation of an automation system for the cocoa almond drying machine at the "ASOPROCANAM" collection center in La Maná, which performs an automatic system of uninterrupted power supply by means of a transfer between the electrical network and a generator set and also performs the automatic control of the cocoa drying temperature. The problem to be solved was that the cocoa drying machine was prone to power outages and failures and the cocoa seed temperature was inefficient. With the implementation, the problem of lack of energy supply, optimal control of the temperature required by the cocoa is solved, thus improving production times and avoiding product pests. The purpose of the automatic drying process is to reduce cocoa drying time losses and improve cocoa drying quality. Controllers were designed and implemented for power supply through automatic transfer with a Siemens LOGO V8 controller and for temperature control through the intelligent temperature supervisor; electrical, mechanical, electronic and electromechanical components were selected and then the control and power circuits of the two systems were designed in CADe SIMU software. With the system in operation, a quality cocoa bean was obtained by controlling the temperature from 50 °C to 75 °C complying with the technical standards of INEN 176 and thus improving the production of cocoa bean drying and also optimizing the useful life of the machine.